2018
DOI: 10.3389/fimmu.2018.00480
|View full text |Cite
|
Sign up to set email alerts
|

CD5L Promotes M2 Macrophage Polarization through Autophagy-Mediated Upregulation of ID3

Abstract: CD5L (CD5 molecule-like) is a secreted glycoprotein that controls key mechanisms in inflammatory responses, with involvement in processes such as infection, atherosclerosis, and cancer. In macrophages, CD5L promotes an anti-inflammatory cytokine profile in response to TLR activation. In the present study, we questioned whether CD5L is able to influence human macrophage plasticity, and drive its polarization toward any specific phenotype. We compared CD5L-induced phenotypic and functional changes to those cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 51 publications
3
74
1
Order By: Relevance
“…The results of the present study demonstrated that I/R induced ROS generation and inhibited antioxidative enzyme activity. A previous study has suggested that CD5L induces anti-inflammatory effects by autophagy (20); therefore, the inhibitory effect of CD5L on oxidative stress was examined in the present study. In accordance with the result of previous study, CD5L inhibited the oxidative stress induced by I/R.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the present study demonstrated that I/R induced ROS generation and inhibited antioxidative enzyme activity. A previous study has suggested that CD5L induces anti-inflammatory effects by autophagy (20); therefore, the inhibitory effect of CD5L on oxidative stress was examined in the present study. In accordance with the result of previous study, CD5L inhibited the oxidative stress induced by I/R.…”
Section: Discussionmentioning
confidence: 99%
“…CD5L is a 40-kDa soluble glycoprotein that belongs to the scavenger receptor cysteine rich superfamily (32). CD5L is involved in a variety of biological processes, such as infection, atherosclerosis and apoptosis (11,20). Various disease models, including cancer, have demonstrated that CD5L participates in cellular functions by preventing apoptosis (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top genes that were upregulated upon IL-33 administration were retnla/Fizz1, Arg1, rnase2, CD5L, prg2, saa3, chil3, and alox15. Interestingly, these genes have been widely implicated in the development of the suppressive, alternatively activated M2 macrophages [28][29][30][31][32]. Therefore, this finding implicates that IL-33 may contribute to the resolution of inflammation partly by upregulating M2-associated markers and polarization.…”
Section: Il-33 Treatments Induced M2-macrophages-related Genes In Nzbmentioning
confidence: 87%
“…For example, C4BP, CHD7, and KLK2 are known as tumour biomarkers, while CD5L, EIF5A1, FINC, and SEPP1 are not only described as biomarkers but also known to participate in tumour progression [31, 33, 57, 81].…”
Section: Discussionmentioning
confidence: 99%